2018
DOI: 10.1002/jhet.3099
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antibacterial Activity of 2‐substitued‐(3‐pyridyl)‐quinazolinone Derivatives

Abstract: A series of 2‐substitued‐(3‐pyridyl)‐quinazolinone derivatives were synthesized, characterized, and evaluated for bacteriostatic activity against three species of phytopathogenic bacteria (Xanthomonas oryzae pv. oryzae, Xoo, Ralstonia solanacearum, and Xanthomonas axonopodis pv. citri, Xac). Biological evaluation showed that compounds 4b, 4g, 4h, 4l, and 4m exhibited higher antibacterial activity than bismerthiazol, the positive control, under conditions. In particular, compounds 4l and 4m exhibited significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…[1][2][3][4][5][6][7] Among heterocyclic compounds quinazolines are well-recognized for their pharmacological properties, such as anticonvulsant [8], antihypertensive [9] and vasodilator [10]. The interest in the quinazolinic structure, due to its wide range of biological activities, [11][12][13][14][15][16][17][18][19] led to a many number of different synthetic pathways to access this quinazolines nucleus. Quinazolinone are divided into subcategories like 2-quinazolinone (a) and 4-quinazolinone (b) based on the substitution on quinazolinones shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Among heterocyclic compounds quinazolines are well-recognized for their pharmacological properties, such as anticonvulsant [8], antihypertensive [9] and vasodilator [10]. The interest in the quinazolinic structure, due to its wide range of biological activities, [11][12][13][14][15][16][17][18][19] led to a many number of different synthetic pathways to access this quinazolines nucleus. Quinazolinone are divided into subcategories like 2-quinazolinone (a) and 4-quinazolinone (b) based on the substitution on quinazolinones shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…Quinazolines have a broad range of pharmacological applications, in addition to their low toxicity profiles [ 3 ]. Quinazoline frameworks have great pharmacological activities as antioxidant [ 7 , 8 , 9 ], antidiabetic [ 10 , 11 , 12 ], antibacterial [ 13 , 14 , 15 ], antiviral [ 16 , 17 , 18 ], antimicrobial [ 19 , 20 , 21 ], anticancer [ 22 , 23 ], antihistaminic [ 24 , 25 , 26 ], antidiuretic [ 27 , 28 ], antitubercular [ 29 , 30 , 31 ], and anti-inflammatory [ 32 , 33 , 34 ] agents. Quinazolinones are a type of quinazoline derivative that are biologically active in the same way as quinazoline [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, quinazolinones have gradually attracted the attention of scholars in the creation of new pesticides. The existing research results showed that quinazolinone derivatives have antiviral, , antibacterial, antifungal, and other activities in the prevention and treatment of plant diseases. As an important pharmacophore of the antibacterial agents, such as fluquinconazole and proquinazid (Figure ), quinazolinone has received high attention due to its simple and variable structure …”
Section: Introductionmentioning
confidence: 99%